Rapid assessment of water availability and appropriate technologies for small-scale farming: guidelines for practitioners - Keller, A.; Weight, Elizabeth; Taylor, S. (International Water Management Institute, 2013)
Limited access to water is a key reason why millions of poor farmers struggle to grow enough food and marketable crops to improve their lives. Public sector agencies, civil society organizations and donors seeking to improve small-scale farmers’ access to water resources face limited data on the location and accessibility of water resources. This paper addresses this gap by providing a tested method to assess water resources that small-scale farmers can access affordably and sustainably. This paper also supports the selection of appropriate water access and application technologies for available water resources. The method described is rapid and relatively inexpensive; it uses a phased approach to assess a broad-scale area (e.g., a country or region); and then gathers more information in locations that have higher potential for affordable water access by small-scale farmers.